Determining the U-Pb emplacement age of lamproites and kimberlites in Southeastern Kansas - Lupini, Isabella (Kansas State University, 2024)
In eastern Kansas, twelve kimberlites and two lamproites constitute the southern portion of a ~5000 km stretch of Mid-Cretaceous-age alkali magmatism in central North America. Four main geodynamic models have been proposed to explain the formation of this alkaline igneous corridor including entrainment by mantle plumes, subduction of the Farallon plate, large low shear velocity provinces, and edge-driven mantle convection cells. Each of these models has temporal constraints that can be used to evaluate their viability. The emplacement ages for the Kansas kimberlites were previously reported by Blackburn et al. (2008) as 110-85 Ma, with a younger hydrothermal reheating event recorded at ~65 Ma. K-Ar geochronology conducted on the Kansas lamproites by Zartman et al. (1967) suggest they are younger than most of the kimberlites, with an age of ~90-88 Ma. However, the limited amount of data and their uncertainty make it difficult to assess the relationship between the two magmatic events. To better constrain the timing of emplacement, we conducted in situ U-Pb perovskite geochronology on the Hills Pond and Rose Dome lamproites, along with reanalysis of the Tuttle and Bala kimberlites. Perovskite was chosen for analysis because it is one of the few primary phases that occurs in both rock types AND has survived the pervasive alteration observed. Our age data for the Kansas kimberlites and lamproites are consistent with previous studies. The Tuttle perovskites yield an age of 105.6 ± 1.9 Ma, which agrees well with the 106.6 ± 1 Ma age determined by Blackburn et al. (2008) using Rb-Sr on megacrystic phlogopite and clinopyroxene. In contrast, the Bala kimberlite yields two arrays on the Tera-Wasserburg concordia diagram, one with an age of 59.6 ± 7.4 Ma and the other 81.7 ± 8.6 Ma. Blackburn et al. (2008) also report two ages for this kimberlite. Their younger age of 64.3 ± 7.5 Ma, based on (U-Th)/He in apatite, is within error of our new perovskite age. However, their older age of 103.0 ± 7.5 Ma, based on (U-Th)/He in magnetite separated from a calcite vein, is more than 20 m.y. older than our older perovskite age. Our petrologic data, in combination with the two perovskite age populations, suggest in contrast to Blackburn et al. (2008), that the Bala kimberlite site sustained reoccurring magmatism for at least ~22 m.y., and possibly longer. The Hills Pond and Rose Dome perovskites yield ages of 86.8 ± 3.5 and 97.1 ± 12.6 Ma, respectively. Thus, the emplacement of the Kansas kimberlites and lamproites overlap in time, but with the initiation of kimberlite magmatism preceding that of the lamproites by at least 8 m.y. The significant time span for the kimberlite and lamproite magmatism is most consistent with an edge-driven convection model of formation.
Keywords: Lamproite; Kimberlite; Perovskite; Edge driven convection; U-Pb geochronology